2009
DOI: 10.1016/j.apenergy.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of free-piston diesel engine combustion

Abstract: This paper investigates the in-cylinder gas motion, combustion process and nitrogen oxide formation in a free-piston diesel engine and compares the results to those of a conventional engine, using a computational fluid dynamics engine model. Enhanced radial gas flow (squish and reverse squish) around top dead centre is found for the free-piston engine compared to a conventional engine, however it is found that this has only minor influence on the combustion process. A higher heat release rate from the pre-mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(53 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…The results showed that the performance of the FPLG had a slight advantage over the conventional engine for faster-burning fuels [14]. In 2009, a computational study was undertaken to investigate the in-cylinder gas motion, combustion process and nitrogen oxide formation in a diesel FPLG [15]. It was found that the in-cylinder gas temperature in the FPLG was lower than that in the CE, which contributed to the decrease of the NO x emission.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the performance of the FPLG had a slight advantage over the conventional engine for faster-burning fuels [14]. In 2009, a computational study was undertaken to investigate the in-cylinder gas motion, combustion process and nitrogen oxide formation in a diesel FPLG [15]. It was found that the in-cylinder gas temperature in the FPLG was lower than that in the CE, which contributed to the decrease of the NO x emission.…”
Section: Introductionmentioning
confidence: 99%
“…A two-stroke operating cycle is usually used in the electrical generators on the basis of a free-piston engines [3,6,7]. There are different types of coupling of the free-piston internal combustion engine and an electric generator [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a number of cold and hot flow CFD simulation studies have been carried out to understand in-cylinder flow field, combustion and emission processes in IC engines [12][13][14][15]. These investigations have shown that complex flow structures like swirl, tumble and turbulence exist inside the engine cylinder, even after the closure of the intake valve [16].…”
Section: Introductionmentioning
confidence: 99%